Pengelolaan Sumber Daya Manusia Dalam Mengembangkan Mutu Pendidikan - Gunawan Gunawan; Noviawati Noviawati; uryadin uryadin; Ulpah Nupusiah; Yudi Saputra; Yayat Hidayat (Peneliti.net, 2022)
The purpose of this study is to find out how the management of human resources in developing the quality of education. This research is a qualitative research that is literature study using data sources in the form of reference books and scientific journal articles. The results of this study are human resource management is very important in improving the quality of education. Education can progress and develop with the support of qualified human resources. Therefore, every education that wants to progress and develop must pay attention to human resources and manage it as well as possible so that quality education is realized. In improving quality, human resources become influential because human resources in this case educators are a central factor in education, considering that it is very important in improving the quality of education. With the use of human resources by managers (leaders) in an organization or educational institution effectively and efficiently, it will take advantage of the goals of the educational institution, and the utilization of human resources starts from proper planning, solid organization, proper and professional staffing, Guidance and supervision that are not properly controlled will ensure the functioning of the managerial process. Human resources are an important factor for the success of an educational institution, for that human resources need to be managed as well as possible through human resource management.